The current state of the art of using Intelligent Systems Applications in interactive language learning. (Eurasian Scientific Herald, 2023)
While the rapid development of technology makes it difficult to keep track of all developments, it also increases the need to stay up-to-date. Following the new and always using the new has become an inevitable need in business life, where change has become one of the most important elements. For this, it is necessary to know the latest technologies and their development status. This is where the state-of-art concept comes into play and characterizes cutting-edge innovation. The development of artificial intelligence technologies continues at a remarkable pace. It is equally important to know which of these technologies are the newest and to get an idea of what we can use them for. In this context, we will take a look at what state-of-the-art AI technologies are and what exactly state-of-the-art means.